Using mobile applications for self-directed learning of academic vocabulary among university students. (2nd October 2022) - Xodabande, Ismail; Atai, Mahmood Reza
ABSTRACT: The current study investigated the contribution of a mobile application for self-directed and autonomous learning of academic vocabulary among English as a Foreign language (EFL) university students. Furthermore, we examined the long-term impacts of mobile-assisted vocabulary learning, by using a pre-, post-, and delayed post-test design. The participants were 38 third- and fourth-year university students in experimental (N = 20) and control (N = 18) groups, selected based on convenience sampling procedures. During a semester, students in the experimental group used a mobile application (i.e. AWL builder), while the control group used traditional materials. The participants' receptive vocabulary knowledge was tested three times. The findings revealed that both groups improved their vocabulary knowledge (Sig. < 0.000). Nonetheless, the participants in the experimental group attained better results in both post- and delayed post-test, and the observed mean differences were statistically significant (Sig. < 0.000, Partial Eta Squared = 0.356). Moreover, a significant effect for time was found for mobile-assisted vocabulary learning (Sig. < 0.000, Partial Eta Squared = 0.907). The results highlight the potential offered by mobile applications for self-directed learning of academic vocabulary and promise implications for EFL vocabulary learning.